Research and information on fish for the developing world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The International Aquatic Resources Management (ICLARM) is an international, nonprofit organization which conducts interdisciplinary research on the management of living aquatic organisms and coastal resources in tropical developing countries. It...